ORGANIZATION OF APPLIED BACCALAUREATE IN COLLEGE OF HUMANITIES AND TECHNOLOGY ON THE BASIS OF CLUSTER APPROACH - Gennadiy A. Melekesov; Natal’ya E. Erofeeva (Высшее образование в России, 2016)
The article is devoted to the implementation of a cluster approach in organizationof practice+oriented education for bachelors at Orsk humanitarian-technological institute. The experience and traditions of engineering and pedagogical staff training is presented in the context of the modern trends of higher education development at the regional university. The prospects of the cluster system are defined based on the regional needs.